2017
DOI: 10.1111/brv.12348
|View full text |Cite
|
Sign up to set email alerts
|

Disruptive physiology: olfaction and the microbiome–gut–brain axis

Abstract: This review covers the field of olfaction and chemosensation of odorants and puts this information into the context of interactions between microbes and behaviour; the microbiome-gut-brain axis (MGBA). Recent emphasis has also been placed on the concept of the holobiome which states that no single aspect of an organism should be viewed separately and thus must include examination of their associated microbial populations and their influence. While it is known that the microbiome may be involved in the modulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 164 publications
0
27
0
Order By: Relevance
“…Olfactory communication is extremely widespread among animals, and facilitates complex social interactions among many vertebrates (Bienenstock, Kunze, & Forsythe, 2018;Wyatt, 2014). The revelation that microbes could be essential to this process forces a rethink of many aspects of behavioural and sensory ecology (Archie & Theis, 2011;Archie & Tung, 2015;Bienenstock et al, 2018). The recognition that microbially mediated olfactory communication is an important driver of vertebrate behaviour has led to a recent call to incorporate olfaction into the microbiome-gut-brain axis (Bienenstock et al, 2018).…”
Section: Microbially Mediated Communicationmentioning
confidence: 99%
See 3 more Smart Citations
“…Olfactory communication is extremely widespread among animals, and facilitates complex social interactions among many vertebrates (Bienenstock, Kunze, & Forsythe, 2018;Wyatt, 2014). The revelation that microbes could be essential to this process forces a rethink of many aspects of behavioural and sensory ecology (Archie & Theis, 2011;Archie & Tung, 2015;Bienenstock et al, 2018). The recognition that microbially mediated olfactory communication is an important driver of vertebrate behaviour has led to a recent call to incorporate olfaction into the microbiome-gut-brain axis (Bienenstock et al, 2018).…”
Section: Microbially Mediated Communicationmentioning
confidence: 99%
“…Microbes may influence behaviour via direct neuronal connections between the gut and the brain, via their effect on physiology (Bienenstock et al, 2018), and via their effect on animal communication, via either the gut or through scent glands . The microbial role in olfactory communication suggests we must reconsider much of what we know about signalling and information theory as it applies to this mode of animal interactions.…”
Section: Microbially Mediated Communicationmentioning
confidence: 99%
See 2 more Smart Citations
“…Since then more groups have observed that in both rats and mice, VPA exposure consistently decreases sociability (Kim et al, ; Kim et al, ; Moldrich et al, ; Roullet et al, ). Additionally, VPA exposure diminishes olfactory discrimination, which can be related to social recognition and development (Bienenstock et al, ; Melo et al, ; Roullet et al, ; Terry and Johanson, ).…”
Section: Btbrmentioning
confidence: 99%